Robotic Control with Pattern Recognition by Dynamic ImageSegmentation - Bruno, Domingos; Melo, Rodrigo; Marques , Francisco das Chagas; Saraiva, Arata; Ferreira, Nuno; Sousa, José (Anais da Escola Regional de Informática do Piauí (ERI-PI), 2018)
This paper creates a methodology capable of performing gesture recognition, where the idea is to extract characteristics of the segmented hand, from dynamic images captured from a webcam, and to identify signal patterns. With the creation of this mechanism it will be possible develop tools to facilitate the manipulation of an robotic arm that performs specific movements. The method used consists of the Continuously Adaptive Mean-SHIFT algorithm, Canny operator and Deep Learning through Convolutional Neural Network. The method obtains a accuracy rate of 97.50% in recognizing the gesture patterns as observed in the statistical data obtained.